Strategic Tools in Regenerative and Translational Dentistry - Marco Tatullo (International Journal of Molecular Sciences, 2019)
Human oral-derived stem cells can be easily obtained from several oral tissues, such as dental pulp, periodontal ligament, from gingiva, or periapical cysts. Due to their differentiation potential, oral-derived mesenchymal stem cells are promising for tissue engineering and regenerative medicine. The regenerative ability showed by some oral tissues strongly depends on their sleeping adult stem cell populations that are able to repair small defects and to manage local inflammation. To date, researchers are working on effective and efficient methods to ensure safe and predictable protocols to translate stem cell research into human models. In the last decades, the challenge has been to finally use oral-derived stem cells together with biomaterials or scaffold-free techniques, to obtain strategic tools for regenerative and translational dentistry. This paper aims to give a clear point of view on state of the art developments, with some exciting insights into future strategies.